Conformational characterization of human eukaryotic initiation factor 2 alpha: a single tryptophan protein - Sreejith, R. K.; Yadav, Viveka Nand; Varshney, Nishant K.; Berwal, Sunil K.; Suresh, C. G.; Gaikwad, Sushama M.; Pal, Jayanta K. (Biochemical and Biophysical Research Communications, 2009)
The alpha-subunit of the human eukaryotic initiation factor 2 (heIF2 alpha), a GTP binding protein, plays a major role in the initiation of protein synthesis. During various cytoplasmic stresses, eIF2 alpha gets phosphorylated by eIF2 alpha-specific kinases resulting in inhibition of protein synthesis. The cloned and over expressed heIF2 alpha, a protein with a single tryptophan (trp) residue was examined for its conformational characteristics using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The steady-state fluorescence spectrum, fluorescence lifetimes (tau(1) = 1.13 ns and tau(2) = 4.74 ns) and solute quenching studies revealed the presence of trp conformers in hydrophobic and differential polar environment at any given time. Estimation of the alpha-helix and beta-sheet content showed: (i) more compact structure at pH 2.0, (ii) distorted alpha-helix and rearranged beta-sheet in presence of 4 M guanidine hydrochloride and (iii) retention of more than 50% ordered structure at 95 degrees C. Hydrophobic dye binding to the protein with loosened tertiary structure was observed at pH 2.0 indicating the existence of a molten globule-like structure. These observations indicate the inherent structural stability of the protein under various denaturing conditions. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Circular dichroism; heIF2 alpha; K562 cells; Molten globule; Steady-state and time-resolved fluorescence

Conformational transitions of the catalytic domain of heme-regulated eukaryotic initiation factor 2 alpha kinase, a key translational regulatory molecule - Sreejith, R. K.; Suresh, C. G.; Bhosale, Siddharth H.; Bhavnani, Varsha; Kumar, Avinash; Gaikwad, Sushama M.; Pal, Jayanta K. (Journal of Fluorescence, 2012)
In mammalian cells, the heme-regulated inhibitor (HRI) plays a critical role in the regulation of protein synthesis at the initiation step through phosphorylation of a-subunit of the eukaryotic initiation factor 2 (eIF2). In this study we have cloned and performed biophysical characterization of the kinase catalytic domain (KD) of rabbit HRI. The KD described here comprises kinase 1, the kinase insertion domain (KI) and kinase 2. We report here the existence of an active and stable monomer of HRI (KD). The HRI (KD) containing three tryptophan residues was examined for its conformational transitions occurring under various denaturing conditions using steady-state and time-resolved tryptophan fluorescence, circular dichroism (CD) and hydrophobic dye binding. The parameter A and phase diagram analysis revealed multi-state unfolding and existence of three stable intermediates during guanidine hydrochloride (Gdn-HCl) induced unfolding of HRI (KD). The protein treated with 6 M Gdn-HCl showed collisional and static mechanism of acrylamide quenching and the constants (K-sv=3.08 M-1 and K-s=5.62 M-1) were resolved using time resolved fluorescence titration. Based on pH, guanidine hydrochloride and temperature mediated transitions, HRI (KD) appears to exemplify a rigid molten globule-like intermediate with compact secondary structure, altered tertiary structure and exposed hydrophobic patches at pH 3.0. The results indicate the inherent structural stability of HRI (KD), a member of the class of stress response proteins.
Keywords: Circular dichroism (CD); eIF2 alpha kinase; Heme-regulated inhibitor; Molten globule; Steady-state and time-resolved fluorescence

Activation of HRI is mediated by Hsp90 during stress through modulation of the HRI-Hsp90 complex - Berwal, Sunil K.; Bhatia, Varsha; Bendre, Arneya; Suresh, C. G.; Chatterjee, Sangeeta; Pal, Jayanta K. (International Journal of Biological Macromolecules, 2018)
Heme Regulated Inhibitor (HRI) is known to get activated in various stresses such as heme deficiency, heat shock, heavy metal toxicity etc. Heat shock protein 90 (Hsp90), a ubiquitous cytoplasmic protein interacts with HRI in order to regulate protein synthesis. However, it still remains to establish this interaction of HRI and Hsp90 at cellular levels and how this modulation of HRI activity is mediated by Hsp90 during stress. In the present report, using co-immunoprecipitation analysis we show that HRI interacts with Hsp90 and this association is independent of other co-chaperones in in vitro conditions. Further, analysis using truncated domains of HRI revealed that the K1 subdomain is essential for HRI - Hsp90 complex formation. Our in silico protein - protein interaction studies also indicated interaction of Hsp90 with K1 subdomain of HRI. Mammalian two hybrid assay validated this HRI - Hsp90 interaction at cellular levels. When the in vitro kinase assay was carried out with the co-immunoprecipitated complex of HRI - Hsp90, an increase in the kinase activity was observed resulting elevated levels of eIF2 alpha phosphorylation upon heavy metal stress and heat shock. Thus, our results clearly indicate modulation of HRI kinase activity with simultaneous Hsp90 association under stress conditions. (C) 2018 Elsevier B.V. All rights reserved.

Cloning and characterization of trehalase: a conserved glycosidase from oriental midge, Chironomus ramosus - Shukla, Ekta; Thorat, Leena; Bendre, Ameya D.; Jadhav, Santosh; Pal, Jayanta K.; Nath, Bimalendu B.; Gaikwad, Sushama M. (3 Biotech, 2018)
Insect trehalase is a multiferous enzyme, crucial for normal physiological functions as well as under stress conditions. In this report, we present a fundamental study of the trehalase gene segment (1587 bp) from Chironomus ramosus (CrTre) encoding for 529 amino acids, using appropriate bioinformatics tools. C. ramosus, a tropical midge is an emerging animal model to investigate the consequences of environmental stresses. We observed that CrTre belongs to GH family 37 in the CAZy database and possess 57-92% identity to dipteran trehalases. In silico characterization provided information regarding the structural, functional and evolutionary aspects of midge trehalase. In the phylogenetic tree, CrTre clustered with the soluble dipteran trehalases. Moreover, domain functional characterization of the deduced protein sequence by InterProScan (IPR001661), ProSite (PS00927 and PS00928) and Pfam (PF01204) indicated presence of highly conserved signature motifs which are important for the identification of trehalase superfamily. Furthermore, the instability index of CrTre was predicted to be < 40 suggesting its in vivo stability while, the high aliphatic index indicated towards its thermal stability (index value 71-81). The modelled 3D tertiary structure of CrTre depicts a (alpha/alpha)(6) barrel toroidal core. The catalytic domain of the enzyme comprised Glu424 and Asp226 as the putative active site residues. Interestingly, the conserved motifs were observed to be formed by the flexible loopy regions in the tertiary structure. This study revealed essential sequence features of the midge trehalase and offers better insights into the structural aspects of this enzyme which can be correlated with its function.
Keywords: Conserved motifs; Homology modelling; Midges; Secondary structure; trehalose

The Leishmania donovani IMPACT-like protein possesses non-specific nuclease activity - Rao, Shilpa J.; Shukla, Ekta; Bhatia, Varsha; Lohiya, Bharat; Gaikwad, Sushama M.; Kar, Anita; Pal, Jayanta K. (International Journal of Biological Macromolecules, 2018)
IMPACT (Imprinted and Ancient)-like proteins are known to be regulators of GCN2 (General control non-derepressible 2) kinases involved in translation regulation. Here, we report on cloning and characterization of an IMPACT-like protein, LdIMPACT from Leishmania donovani which harbours two domains. 'RWD domain' at the N-terminal end that mediates GCN2 regulation, while a conserved 'ancient domain' lies at the C-terminal end whose function remains elusive. Interestingly, our observations indicated that LdIMPACT has a novel nonspecific nuclease activity. In silico analysis further revealed the resemblance of ancient domain of LdIMPACT to RNase PH domain (known to bind to nucleic acids). The recombinant LdIMPACT exhibited a Mg2+-dependent nuclease activity. Moreover, thermostability and pH stability assays of the protein suggest it to be a stress responsive protein. Circular dichroism studies elucidated the conformational transitions of the enzyme in response to various temperature and pH conditions which correlated well with the activity profiles. Thus, the current study highlights the structural and functional characteristics of LdIMPACT which interestingly also possesses a novel nuclease activity. With its physiological relevance unresolved, the multifaceted LdIMPACT might therefore lie in a hitherto unknown network, whose perturbation could be an attractive therapeutic approach for treating leishmaniasis. (C) 2018 Elsevier B.V. All rights reserved.